2016
DOI: 10.1007/s13340-016-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status is associated with mild cognitive impairment assessed with the mini-mental state examination in Japanese diabetic patients

Abstract: Aims We assessed the association between smoking status and mild cognitive impairment (MCI) in Japanese diabetic patients. Methods This cross-sectional study included 323 diabetic patients, aged 40-79 years, who were referred to an out-). Cognitive function was assessed using the minimental state examination (MMSE), and patients were classified into two categories: normal cognitive function (MMSE score C27) and MCI (MMSE score 22-26). Logistic regression analysis was used to estimate the multivariable-adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Although there is inconsistency for the gender differences for the incidence rate of cognitive impairment, however, more studies have reported a higher prevalence of cognitive impairment in women [ 22 24 ]. Our study also showed that smoking and glycated hemoglobin were strongly associated with cognitive impairment in patients with T2DM, the results are consistent with previous reports [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although there is inconsistency for the gender differences for the incidence rate of cognitive impairment, however, more studies have reported a higher prevalence of cognitive impairment in women [ 22 24 ]. Our study also showed that smoking and glycated hemoglobin were strongly associated with cognitive impairment in patients with T2DM, the results are consistent with previous reports [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Both AC and WC were predictors of cognitive performance in women and men, but BMI was only a predictor in women. On multivariate analysis for age, smoking status (2729), and BMI or WC or AC values, all three body measurements remained significant predictors of cognitive performance in women (p<0.001, p=0.003, p<0.001, respectively). In men, only BMI (p=0.013) and AC (p<0.001) were independent predictors.…”
Section: Resultsmentioning
confidence: 98%
“…The correlation of the WC with an ADL score was also extremely weak in both sexes together and in men ( r s = 0.04, p < 0.01; r s = 0.09, p < 0.001, respectively), while in women no correlation existed. Next, we performed the multivariable analysis with age, sex, and smoking status as co-variates selected based on the literature data [ 34 , 35 , 36 ]. The analysis revealed that both body measurements remained independent predictors of an ADL score (BMI: p < 0.001, WC: p < 0.05).…”
Section: Resultsmentioning
confidence: 99%